RESTORATIVE JUSTICE AND THE PROTECTION OF GENDER-BASED VIOLENCE VICTIMS IN THE INTER-AMERICAN COURT: EVOLUTION AND PERSPECTIVES - Tripo, Francesco (2025)
Restorative justice is gaining increasing relevance within the Inter-American human rights system, emerging as a complementary—and in some cases, alternative—paradigm to traditional retributive justice.